PENGARUH PENGETAHUAN ANGGOTA DPRD TENTANG ANGGARAN, PEMAHAMAN REGULASI DAN PENGALAMAN TERHADAP PERAN ANGGOTA DEWAN DALAM PENGAWASAN KEUANGAN DAERAH (Studi Pada DPRD Pemerintahan Provinsi Riau) - Kharimah, Firda; Tanjung, Amries Rusli; ', Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The research aims to analyze of influencing of knowledge legislators about budgeting, understanding the regulation and experience to the role of legislators in the area of financial supervision. Object of this research is DPRD Riau Province. There are forty four questionnaires were sent, but only forty four questionnaires are returned. That data are analyzed by linear regression method and SPSS program version 19. The variables were examined influencing of knowledge legislators about budgeting, understanding the regulation and experience to the role of legislators in the area of financial supervision. The results of this research showedinfluencing of knowledge legislators about budgetinghas an effect tothe role of legislators in the area of financial supervision with 0,000 significance, understanding the regulation has an effect tothe role of legislators in the area of financial supervision with 0,002 significance and experiencehas an effect tothe role of legislators in the area of financial supervisionwith 0,000 significance. The results of this research also showed that coefficient R square is 72,2%. Each independent variables, gives the strong influence to dependent variable, it means independents variables could explain dependent variable well. While the remaining influenced by other variables not included in the regression models were not included in this study. All variables also have strong relation with variable dependents in this research.Keywords: Knowledge, Budgeting, Regulation, Experience, and Supervision